Short-term outcomes following congenital heart surgery in children with Down syndrome - Tri Yanti Rahayuningsih; Sukman Tulus Putra; Piprim Basarah Yanuarso; Zulham Effendy (Indonesian Pediatric Society, 2023)
Background Children with Down syndrome (DS) differ from typical children because of many genetic-related aspects that may affect outcomes after congenital heart surgery. To date, there have been no studies on outcomes after congenital heart surgery on pediatric DS patients in Indonesia. Objective To determine outcomes and mortality in DS patients who underwent heart surgery at Dr. Cipto Mangunkusumo Hospital, Jakarta. Methods A prospective and retrospective cohort study was conducted in DS patients aged <15 years who underwent heart surgery from July 2007 to April 2015. The control group were patients in the same age range without DS who underwent heart surgery for various types of heart defects. Results There were 57 DS and 43 non-DS patients during study period. The types of heart defects found in DS patients were atrioventricular septal defect (AVSD) and ventricular septal defect (VSD) in 18/57 (31.6%) patients each, tetralogy of Fallot (12/57; 21%), atrial septal defect (ASD) (4/57; 7%), patent ductus arteriosus (PDA) (4/57; 7%) and transposition of the great arteries with VSD (TGA-VSD) (1/57; 1.8%). DS patients showed an increased incidence of preoperative PH (63.1%) compared to non-DS patients (25.6%). Median duration of surgery was longer in DS [2.9 (range 0.5-5.8) hours] than in non-DS [2.2 (range 0.7-4.7) hours]. DS patients have a longer mean cardiopulmonary bypass duration [79.5 (SD 33.9) minutes] compared to non-DS [59.9 (SD 23.6) minutes], longer mean aortic cross-clamp duration [45.3 (SD 23.7) minutes] compared to non-DS [34.8 (SD 15.7)]. There were significant differences in the incidence of preoperative pulmonary hypertension, surgical time, duration of cardiopulmonary bypass (CPB), and length of the aortic cross-clamp in DS patients compared to non-DS (P<0.05). Median length of ICU stay was 1.9 (range 0.6 to 34) days in DS and 1 (range 0.3 to 43) day in non-DS patients (P=0.373). Median duration of mechanical ventilation [19.9 (range 3-540) vs. 8 (range 3-600) hours (P=0.308)], rate of pulmonary complications [14/57 (24.6%) vs. 6/43 (14%) patients (P=0.216)], and incidence of sepsis [16/57 (28.1%) vs. 6/43 (14%) patients (P=0.143)] were not significantly different between DS and non-DS patients. However, complete atrioventricular (AV) block only occurred in DS patients [6/57 (10.5%)]. In the DS group, 5/57 (8.8%) patients died. There was no mortality in the non-DS group. Conclusion Morbidity and mortality after cardiac surgery in were higher in DS than in non-DS patients. DS patients may have problems related to preoperative PH, AV block, longer surgical time, duration of CPB, and aortic cross-clamp compared to non-DS.